Implementasi peraturan daerah Kabupaten tulungagung nomor 1 tahun 2020 Tentang penyelenggaraan dan pelayanan pasar - Husin Husin; Imam Fachruddin; Muhamad Chairul Basrun Umanailo (Universitas Medan Area, 2023)
This research is motivated by the author's interest in seeing how traditional markets in modern times like today and in Islam recommend that everything should be neat, correct, orderly and orderly. The existence of traditional markets is one of the important sectors that support the people's economy. The negative image of traditional markets is identical to the poor physical aspects of buildings, management and slum management. Regional Regulation Number 1 of 2020 concerning Market Implementation and Services is one of the regional regulations made by the regional government of Tulungagung Regency which is used to regulate macro-wise how market arrangements can be implemented. This study uses a descriptive type of research with a qualitative approach, because the researcher wants to present the results of the study by describing the actual situation. Data collection techniques using interviews with selected informants, namely the Head of UPT Pasar Rakyat Ngemplak, fruit, vegetable and pracang tradersThe results of the study found that the implementation and service at the Ngemplak People's Market, Tulungagung Regency based on Regional Regulation Number 01 of 2020, went well and was in line with expectations. The determining factors for the success of the Implementation and Service of the Ngemplak People's Market in Tulungagung Regency based on Regional Regulation Number 1 of 2020 are: communication, resources, disposition, bureaucratic structure, Social, Political and Economic Conditions as well as standards and targets.